A spectral collocation method for nonlinear fractional boundary value problems with a Caputo derivative - Wang, Chuanli (2020)
In this paper, we consider the nonlinear boundary value problems involving the Caputo fractional derivatives of order α∈ (1 , 2) on the interval (0, T). We present a Legendre spectral collocation method for the Caputo fractional boundary value problems. We derive the error bounds of the Legendre collocation method under the L2- and L∞-norms. Numerical experiments are included to illustrate the theoretical results.